STRUCTURE OF THE RETE TESTIS OF THE CAT (FELIS-DOMESTICA, L) - Viotto, M. J. S. [UNESP]; Orsi, A. M.; Dias, S. M.; Newmann, H. K. (Gustav Fischer Verlag Jena, 1991)
The rete testis of the cat consists of 3 parts: a septal or interlobular part; a mediastinal part and a tunical part. The septal part contains the septal or transitory tubuli recti and the tubuli recti. The transitory tubules are formed as a confluence of the seminiferous tubules at the apex of the testicular lobules and the tubuli recti. The mediastinal rete is formed of long, straight channels which increase in size and become more irregular and anastomotic below the tunica albuginea at the cranial extremity of the testis. The end is characterized as the tunical part of the rete testis and communicates with the extratesticular rete testis. The channels all parts of the rete are lined by simple cuboidal or columnar epithelium. These epithelial channels are supported by a connective tissue containing smooth muscle cells. The framework tissue of the rete is more conspicuous at the cranial extremity of the testis, with a mio-connective matrix organization.
Keywords: RETE TESTIS; FELIS-DOMESTICA L